Twist of taste: gastronomic allusions in medicine. Issue 2 (9th July 2014) - Lakhtakia, Ritu
Abstract : Food imageries that have inspired and embellished medical learning are, distressingly, vanishing from medical writings. A host of references to the aromas, shape, colour and texture of food have reinforced and stimulated generations of physicians to identify and understand disease. They have piqued interest in foods from lands afar and introduced an unsought dimension and enrichment to the medical lexicon. It is time to revisit this powerful tool and secure its place in medical teaching and records.